Theorizing revolution in democracies: Evidence from the 2019 uprisings in Lebanon and Iraq - Chantal E. Berman; Killian Clarke; Rima Majed (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2023)
Scholarly logic holds that revolutionary movements are unlikely to break out in democracies, where citizens may simply remove unpopular leaders through elections. And yet the twenty-first century has witnessed a global series of uprisings against regimes that are nominally democratic-in that they regularly hold competitive elections-but are otherwise deeply broken, run by kleptocratic networks of elites who often fail to deliver vital services. This paper therefore takes on the task of theorizing revolution in democracy, pointing to some of the ways in which these movements differ from well-studied revolutionary movements in consolidated autocracies. We analyse two recent cases-the Tishreen uprising in Iraq (2019-20) and the Lebanese Thawra (2019-20)-and draw on original protest event catalogues constructed from local Arabic-language newspapers. We argue that the decentralized nature of these regimes may paradoxically render the task of deposing them via mass mobilization more difficult. We investigate mechanisms including the difficulty of sustaining a broad anti-regime coalition in the absence of a singular dictator, the ability of elites to offer resignations without fundamentally altering underlying power structures, and the possibility for an array of non-state and semi-state repressive actors to repress protests.
Keywords: 330; Lebanon; Iraq; protest; revolution; democracy; protest event catalogue